2016
DOI: 10.1021/acs.est.6b00626
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Evidence for Reductive Immobilization of Uranium Across a Roll-Front Mineral Deposit

Abstract: 15We use uranium (U) isotope ratios to detect and quantify the extent of natural U reduction in 16 groundwater across a roll front redox gradient. Our study was conducted at the Smith Ranch-17 model that evaluates both the migration of U from the ore body and the extent of natural 27 attenuation due to reduction. We find that the pre-mining migration of U down-gradient of the 28 delineated ore body is minimal along eight transects due to reduction in or adjacent to the ore 29 body, whereas two other transects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 69 publications
(154 reference statements)
2
32
0
Order By: Relevance
“…Several studies have used δ 238 U to quantify the reduction of U(VI) in groundwater related to U mining and environmental contamination (5,7,50). In most studies the inferred U isotopic fractionation factor is significantly smaller than (e 238 U) 1.3‰, the theoretical NFS value.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have used δ 238 U to quantify the reduction of U(VI) in groundwater related to U mining and environmental contamination (5,7,50). In most studies the inferred U isotopic fractionation factor is significantly smaller than (e 238 U) 1.3‰, the theoretical NFS value.…”
Section: Resultsmentioning
confidence: 99%
“…While the magnitude of U isotope fractionation is consistent with U reduction, quantifying the amount of reductive U precipitation compared with adsorption or other nonfractionating mechanisms is still a challenge. Applying our speciation-fractionation model to the groundwater at the Smith Ranch-Highlands U mine (7), we calculate an effective e 238 U 0.7‰, similar to the value 0.78‰ inferred from variations in the δ 238 U of site groundwater (7). The agreement between the observed and calculated e 238 U suggests that at this particular site the removal of aqueous U(VI) from groundwater is primarily by reduction and that adsorption and hydrodynamic dispersion effects are small.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, non-crystalline U (IV) species with a structure lacking the features of a U–U pair correlation were observed within a sediment sample collected from an ISR U mine following 5 years of post-mining restoration24. Finally, the heavy U isotope signature identified in groundwater and uranium ore concentrates from low-temperature sandstone ore formations suggests that biological reduction maybe a dominant process in those systems252627. Thus, these new developments in environmental speciation of reduced U and U isotope interpretations call for re-evaluation of the prevailing model for U ore formation in roll-front deposits in order to optimize ore exploration and exploitation, as well as mine restoration.…”
mentioning
confidence: 90%
“…WoldeGabriel et al (2014) suggested that pyrite surfaces that are accessible to migrating groundwater could act as reductants to limit the migration of U; consequently, solid-phase aquifer characterization studies are critical in examining the potential for natural attenuation (see US EPA, 2007a). In addition, recent work by Basu et al (2015) indicates that isotopic tracers such as mining has ended as a probe of natural attenuation processes (see also Brown et al, 2016). A range of geochemical pathways have been studied that show promise for transforming uranium to less mobile forms, including co-precipitation with iron oxides (e.g., Duff et al, 2002;Nico et al, 2009;Marshall et al, 2014), co-precipitation with phosphate (e.g., Mehta et al, 2015), and reduction by iron-or sulfur-containing minerals (e.g., Moyes et al, 2000;Scott et al, 2005;Hyun et al, 2012;Troyer et al, 2014).…”
Section: Post-isr Aquifer Restorationmentioning
confidence: 99%